Preliminary Findings on the Foraging Ecology of a Northern Bobwhite Predator in North Florida: The Cooper's Hawk (Accipiter cooperii) - Brian A. Millsap; Timothy Breen; Lora Silvmania (National Quail Symposium Proceedings, 2017)
As part of a larger study of the ecology of the Cooper's hawk (Accipter cooperii) in the Northern Highlands and Red Hills regions of North Florida, we collected data on landscape-level habitat selection, home range size, and diet of resident adult Cooper's hawks from April 1996-April 1997 on study areas in northern Leon County (Tall Timbers Research Station) and western Suwannee County. Data on habitat selection and home range size were collected by intensively tracking 8 radio-instrumented adult Cooper's hawks (3 males and 5 females) originally captured while breeding at nest sites on the study areas. Diet information on the study areas was obtained by observing Cooper's hawk prey deliveries at nest sites from blinds, by collecting prey remains from prey handling perches around nests, and by documenting prey captures by radio-tagged hawks. In this poster we present some preliminary findings from the first year of this study that may have implications for wildlife managers wanting to minimize rates of predation on bobwhites by Cooper's hawks.